Home-Based Aerobic Interval Training Combined with Resistance Training Improved Daytime Dysfunction in Adults with Obesity and Sleep-Disordered Breathing - Longlalerng, Khomkrip; Watanasiripakdee, Siripan; Jeenduang, Nutjaree; Habuddha, Valainipha; Piya-amornphan, Nitita; Damchuai, Tipwamol (Sleep Science, 2024)
Introduction There have been many barriers to exercising at a gym due to the coronavirus disease 2019 (COVID-19) pandemic worldwide. Home-based aerobic interval training (AIT) combined with resistance training (RT) may be helpful for obese adults with sleep-disordered breathing (SDB) to overcome those barriers and improve their subjective sleep disorders. Thus, the present study aimed to examine the effects of home-based AIT combined with RT on subjective sleep disorders in obese adults with SDB.Material and Methods This study has a one-group pretest-posttest design. Twenty-one adults with obesity and SDB were assigned to perform 8 weeks of AIT combined with RT. Subjective sleep disorder variables including the Pittsburgh Sleep Quality Index (PSQI), Berlin Questionnaire, and Epworth Sleepiness Scale were defined as primary outcomes. Anthropometric variables, physical fitness components, and blood biomarkers were assigned as secondary outcomes. All outcome measurements were examined at baseline and after 8 weeks of training.Results Daytime dysfunction of PSQI was significantly improved after 8 weeks of the exercise program (p < 0.05). Upper and lower chest expansion and estimated maximum oxygen consumption were significantly increased after 8 weeks of the exercise program (all p < 0.05). None of the blood biomarkers changed after 8 weeks of training.Conclusion This study suggests that home-based AIT combined with RT effectively alleviates daytime dysfunction and seems to be more helpful in improving global PSQI in adults with obesity. Future studies with a larger sample size, under a controlled trial are recommended to prove the benefits of the exercise program.
Keywords: physical fitness; exercise; sleep quality; resistance training